1996
DOI: 10.1126/science.274.5287.602
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cell-Surface Association Between Fusin and the CD4-gp120 Complex in Human Cell Lines

Abstract: Accessory cell-surface molecules involved in the entry of human immunodeficiency virus-type 1 into cells have recently been identified and shown to belong to the family of chemokine receptors. Treatment of human cell lines with soluble monomeric gp120 at 37 degrees C induced an association between the surface CD4-gp120 complex and a 45-kilodalton protein, which can be down-modulated by the phorbol ester phorbol 12-myristate 13-acetate. The three proteins were coprecipitated from the cell membranes with antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
241
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(259 citation statements)
references
References 12 publications
15
241
1
2
Order By: Relevance
“…Phosphorylation of the cytoplasmic tail of CXCR4 is likely responsible for the down-regulation of CXCR4, but this contention will have to be confirmed by substitution mutations of the PKC sites on the receptor. PMA-induced down-regulation of CD4 in the presence of GP120 required an accessory protein and it was recently shown that this accessory protein is likely CXCR4 (44,45). The results presented here suggest that this down-regulation may involve phosphorylation on the cytoplasmic tail of CXCR4.…”
Section: Fig 4 Desensitization Of Cxcr4supporting
confidence: 45%
“…Phosphorylation of the cytoplasmic tail of CXCR4 is likely responsible for the down-regulation of CXCR4, but this contention will have to be confirmed by substitution mutations of the PKC sites on the receptor. PMA-induced down-regulation of CD4 in the presence of GP120 required an accessory protein and it was recently shown that this accessory protein is likely CXCR4 (44,45). The results presented here suggest that this down-regulation may involve phosphorylation on the cytoplasmic tail of CXCR4.…”
Section: Fig 4 Desensitization Of Cxcr4supporting
confidence: 45%
“…CXCR4 and CCR5 are present as homodimers and heterodimers at the plasma membrane (18)(19)(20). In addition, gp120-mediated CD4/CXCR4 and CD4/CCR5 association and clustering is reported (21)(22)(23). Nonetheless, little is known of how CCR5 expression influences the CD4/CXCR4 interaction, or of the molecular basis that underlies the differences in X4 strains infection relative to CCR5 levels at the cell surface.…”
mentioning
confidence: 99%
“…The receptor for stromal derived factor-␣ (SDF-1␣), CXCR4, appears to act as the primary coreceptor for entry of T-cell tropic strains of HIV (5), whereas CCR5, which functions as the receptor for the chemokines RANTES, MIP-1␣ and MIP-1␤, mediates entry of macrophage or M-tropic viruses (6). The simultaneous interaction of HIV envelope protein (gp120) with both the CD4 receptor and a chemokine receptor is required for viral entry, after exposure of a chemokine receptor-binding determinant mediated by the initial interaction of gp120 with CD4 (7)(8)(9)(10). However, there are examples of chemokine receptordependent but CD4-independent entry of virus (11)(12)(13)(14).…”
mentioning
confidence: 99%